Relación entre la entrada de turistas y el ingreso de divisas por turismo al Perú durante el periodo 2017 – 2021 - Oyarce Vela, Magnolia de Jesús (2024)
Tourism is an activity that, properly carried out, can generate significant income for the country and the communities near the location of the tourist attraction. This master's thesis aims to determine the relationship between the entry of tourists and the income of foreign currency from tourism to Peru during the period 2017 - 2021. With this purpose, this Quantitative research is developed according to its nature, and Correlational according to the explanation, counting for that with a Non-Experimental design. The following conclusions are reached: the existence of a direct relationship between the entry of tourists to the country and the income of foreign currency from tourism during the period 2017 - 2021 is demonstrated, having achieved a Correlation Coefficient of r = 0.994341878; and a Coefficient of Determination of R2 = 0.988715771. Likewise, Jorge Chávez Airport (El Callao) is the main entry point for tourists to Peru, having been used by 59.55% of visitors. The analysis of the country of origin of the tourists shows that the majority come from Chile, representing 26.70% of the total, and not the United States of America as was initially believed, since it ranked second in importance with 15.54%. The overnight stays occurred mainly in Uncategorized lodging establishments, reaching a total of 258,832,687, which represents 75.46% of the total.